2010
DOI: 10.1007/s10237-010-0259-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of elastin anisotropy in structural strain energy functions of arterial tissue

Abstract: The vascular wall exhibits nonlinear anisotropic mechanical properties. The identification of a strain energy function (SEF) is the preferred method to describe its complex nonlinear elastic properties. Earlier constituent-based SEF models, where elastin is modeled as an isotropic material, failed in describing accurately the tissue response to inflation-extension loading. We hypothesized that these shortcomings are partly due to unaccounted anisotropic properties of elastin. We performed inflation-extension t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
(42 reference statements)
2
37
1
2
Order By: Relevance
“…Several groups analyzed biomechanical properties of arteries after selective elimination of elastin and collagen [32,33,34,35]. They reported the existence of significant elastin-dependent compressive pre-stresses (also termed residual stress [36]) within the aortic wall. Interlaminar elastic structures could be responsible for this prestress.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups analyzed biomechanical properties of arteries after selective elimination of elastin and collagen [32,33,34,35]. They reported the existence of significant elastin-dependent compressive pre-stresses (also termed residual stress [36]) within the aortic wall. Interlaminar elastic structures could be responsible for this prestress.…”
Section: Discussionmentioning
confidence: 99%
“…The opening angle measurement is necessary for calculating stress and strain distributions through the wall thickness 12 . The complete set of six test protocols and the opening angle can be used to fit constitutive equations and fully characterize the mechanical behavior of each artery [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The protocol takes more time and effort than a single pressure-diameter or contractility protocol, but provides enough information to compare the behavior for any loading condition and may highlight subtle differences in mechanical behavior that are not apparent in traditional pressure myograph experiments. Microstructurally-based constitutive equations can be used to correlate the mechanical behavior with measured differences in matrix protein amounts or organization [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…In a first approximation, we consider the arterial wall as a linear elastic isotropic material, although it is known that the arterial tissue has a nonlinear stress-strain relation [3], behaves viscoelastically [4,40] and has anisotropic properties [26]. These limitations will be addressed in the discussion in Sect.…”
Section: Arterial Pressure Pulse and Arterial Wallmentioning
confidence: 99%
“…Because this effect is apparently of minor importance, it was neglected. (c) Rezakhaniha et al [26] showed that both collagen and elastin, which are the main constituents of the arterial wall together with smooth muscle cells, exhibit anisotropic properties. The authors achieved an excellent agreement between theory and inflationextension experiments by accounting for this behaviour in the modelling of arterial wall mechanics.…”
Section: Limitations Of Our Analytical Approachmentioning
confidence: 99%